Prevalence and incidence of cancer amongst adults with intellectual disability: a systematic review and meta-analysis protocol [version 2; peer review: 2 approved] - (:unkn) unknown (HRB Open, 2024)
Background: People with intellectual disabilities have poorer health and die earlier than their peers without identified disabilities. This difference represents a significant inequality. Until recently, it was considered that cancer was less common in this population, mainly because they did not live long enough to develop age-related cancers. However, recent evidence has identified that people with intellectual disabilities may be at an increased risk of developing cancer but more likely to present for medical treatment at a later stage when cancer has spread. Nonetheless, the evidence is lacking and there is a need to understand the prevalence and incidence of cancer and subtypes of cancer in adults with intellectual disabilities. Methods A systematic review and meta-analysis will be undertaken to investigate the prevalence and incidence of cancer and subtypes of cancer in adults with an intellectual disability. The JBI Systematic reviews of prevalence and incidence and the PRISMA-P (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed to develop this protocol. Electronic databases will be searched using predefined search terms to identify relevant studies using the Condition Context Population (CoCoPop) framework. Eligible studies should be observational and have published baseline data that have estimated or presented data on the prevalence or incidence of cancer in adults with intellectual disability. To assess the methodological quality of studies included in this review a modified version of the JBI Critical Appraisal Checklist for Studies Reporting Prevalence Data will be used. Prevalence and incidence proportions will be analysed separately with individual study data being pooled using the DerSimonian-Laird proportion method and a random effects meta-analysis will be undertaken. Discussion: This review will advance the epidemiological evidence to identify where targeted cancer care interventions are needed to help reduce the inequalities that this population experiences.
Keywords: Intellectual disability; cancer; neoplasms; systematic review; Ageing; Cancer; Inclusive Society; Health outcomes; INTELLECTUAL DISABILITIES; Intellectual Disability; Intellectual Disability